Role of FoxO3 transcription factor in right ventricular remodeling and failure - Nayakanti, Sreenath Reddy; Justus Liebig University Giessen (My University, 2022)
Background: The functional state of the right ventricle (RV) is the primary determinant of prognosis in pulmonary arterial hypertension (PAH) patients. RV hypertrophy (RVH) triggered by pressure overload is initially compensatory but often leads to RV failure. The Forkhead family of transcription factors mediates many aspects of physiology, including stress response, metabolism and apoptosis. In this study, our objective is to understand the role of FoxO3 and outcomes of FoxO signaling modulation under normal and pathological states of RV in the context of PAH. Methods and Results: We employed pulmonary artery banding (PAB) and monocrotaline (MCT) animal models to induce RV hypertrophy and RV failure in rats and mice. In addition, human RV tissues from healthy, cRV and dRV patients were screened. Echo, invasive hemodynamic measurements and molecular analysis were performed after 5 weeks in PAB- and sham-operated mice. FOXO3 is upregulated in compensated RVs and downregulated in decompensated RVs. FoxO3 is dephosphorylated in RVs from rats subjected to PAB. Human Cardiac Fibroblasts (HCFs) exposed to stiffness and hypoxia led to decreased total FoxO3 levels and increased phosphorylation, suggesting FoxO3’s role in the pathogenesis of PAH. Upon PAB, a decrease in cardiac function was observed in global and fibroblast-specific knockout (Fb-FoxO3-/-) mice. RNA-seq analyses of HCFs upon depletion of FoxO3 revealed upregulation of ECM genes. Furthermore, FoxO3 activation using trifluoperazine (TFP) improved established PAH in the Sugen-hypoxia (Su-Hx) and Monocrotaline (MCT) rats. Conclusions: Our study implicates FoxO3 as a critical integrator of pro-fibrotic and pro-inflammatory signaling in the pathogenesis of RV dysfunction and pharmacological modulation of FoxO3 could serve as a novel therapeutic strategy for PAH patients.
Keywords: ddc:570; ddc:610